Max Dvořak and the founding of the “Ljubljana School of Art History” - Katja Mahnič (Journal of Art Historiography, 2022)
France Stele, Vojeslav Mole and Izidor Cankar, who are considered the founders of Slovenian art history as a modern scientific discipline, were all students of Max Dvořak. Traces of the relationship between Dvořak and his three Slovenian students and of his influence over them can be found in different types of sources. I first focus on the preserved personal and intimate documents, their mutual correspondence and on their autobiographical and biographical texts in which we can learn a great deal about Dvořak as a person and teacher. Then I turn to the “historiographical” texts among which Stele’s texts hold a special place; in them he outlined the process of forming the “Ljubljana School of Art History” and defined the origins of its conceptual and methodological framework with one of its key foundations being the ideas of Dvořak.